2007
DOI: 10.1002/ccd.21353
|View full text |Cite|
|
Sign up to set email alerts
|

The safety and efficacy of an extravascular, water‐soluble sealant for vascular closure: Initial clinical results for Mynx™

Abstract: The initial experience with the extra-arterial Mynx closure technology supports hemostatic safety and efficacy in patients undergoing diagnostic and interventional catheterization procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 57 publications
1
33
1
Order By: Relevance
“…The Mynx water-soluble sealant system was studied in a multicenter single-arm study of 190 consecutive patients undergoing diagnostic and interventional procedures (5F to 7F). 44 The device was found to have a major complication rate of 0.5% in this low-to intermediate-risk population. A randomized study using the procoagulant pads Chito-Seal (Abbott Vascular Devices) and the Clo-Sur (Medtronic Vascular, Santa Rosa, Calif) compared with manual compression for patients undergoing PCI found only a slightly reduced time to hemostasis with procoagulant pad use without an effect on overall bed-rest time or vascular complications.…”
Section: Evidence For Passive-closure Devicesmentioning
confidence: 78%
“…The Mynx water-soluble sealant system was studied in a multicenter single-arm study of 190 consecutive patients undergoing diagnostic and interventional procedures (5F to 7F). 44 The device was found to have a major complication rate of 0.5% in this low-to intermediate-risk population. A randomized study using the procoagulant pads Chito-Seal (Abbott Vascular Devices) and the Clo-Sur (Medtronic Vascular, Santa Rosa, Calif) compared with manual compression for patients undergoing PCI found only a slightly reduced time to hemostasis with procoagulant pad use without an effect on overall bed-rest time or vascular complications.…”
Section: Evidence For Passive-closure Devicesmentioning
confidence: 78%
“…Published results with Mynx™ have varied; some report that it is safe and effective [11][12][13] , while others reported significant complication rates with the first generation device 14,15 . In our study, one minor complication was reported (1.8%) which is at the lower range of reported results using manual compression (1.5% to 9 %, 16,17 ), slightly higher than those of angioSeal™ (0.13 to 1.4) 18 , and almost equal to Starclose (1.9%) 19 .…”
Section: Resultsmentioning
confidence: 99%
“…This combination of safeguards has been reported to make it "virtually impossible to push [the sealant] forward into the artery." 1 The main publication reporting the results of the use of the current-generation Mynx vascular closure device is a prospective nonrandomized trial based in Europe. 1 In this study of 190 patients, rapid hemostasis was achieved (mean, 1.3 minutes) with a success rate of 93%.…”
Section: Discussionmentioning
confidence: 99%
“…This experience led us to try the Mynx vascular closure device, which was reported to be safe and effective and to result in very little pain at the time of deployment. 1 To our knowledge, angiographic or sonographic evaluation of the femoral artery following deployment of the Mynx closure device has not been reported. In this article, we describe the results of follow-up femoral arteriography in the subset of patients in whom the femoral artery was visualized after initial closure with the Mynx device.…”
mentioning
confidence: 93%